Landasan Filosofis dalam Kebijakan Pendidikan Islam: Perspektif Epistemologis - Marlina, Elvia Hani; Nugraha, Mulyawan Safwandy (Universitas Pahlawan Tuanku Tambusai, 2025)
Islamic education serves as a fundamental foundation in shaping individuals who are spiritually, morally, and intellectually balanced. This research explores the concept of Islamic education, emphasizing the integration of knowledge, faith values, and character formation. The introduction discusses the importance of education as a primary means for internalizing religious and moral values in daily life. The study material examines the main pillars of Islamic education: tauhid (monotheism), character building, and intellectual development. By focusing on these aspects, the research highlights the role of education in forming intellectually capable yet morally upright individuals. In conclusion, Islamic education integrates spiritual, moral, and intellectual dimensions to create individuals who are balanced in both worldly and hereafter matters. This research underscores the importance of a holistic approach to education that prioritizes a balance between worldly knowledge and religious values.